Chlamydia trachomatis Infections: Implications for Pregnant Adolescents and Their Infants - Marlene Melzer-Lange; Laurie Good; Halim Hennes (Hindawi Limited, 1994)
Objective: Chlamydia trachomatis infections are common in pregnant adolescents. Previous studies have shown that treating pregnant women of all ages with erythromycin prevents transmission of this infection to their infants. However, there are no published studies on the efficacy of aggressive screening and treatment of C. trachomatis in pregnant adolescents. This study was undertaken to determine if aggressive screening for C. trachomatis in pregnant adolescents and early treatment with erythromycin can prevent complications in their newborn infants.